American orchestras in the nineteenth century - Spitzer, John (University of Chicago Press, 2012)
Studies of concert life in nineteenth-century America have generally been limited to large orchestras and the programs we are familiar with today. But as this book reveals, audiences of that era enjoyed far more diverse musical experiences than this focus would suggest. To hear an orchestra, people were more likely to head to a beer garden, restaurant, or summer resort than to a concert hall. And what they heard weren & rsquo;t just symphonic works & mdash;programs also included opera excerpts and arrangements, instrumental showpieces, comic numbers, and medleys of patriotic tunes. This book brings.